Long-Term Effectiveness of a Stress Management Intervention at Work: A 9-Year Follow-Up Study Based on a Randomized Wait-List Controlled Trial in Male Managers. (18th October 2017) - Li, Jian; Riedel, Natalie; Barrech, Amira; Herr, Raphael M.; Aust, Birgit; Mörtl, Kathrin; Siegrist, Johannes; Gündel, Harald; Angerer, Peter
Abstract : Objective. Short- and medium-term effectiveness (up to 3 years) of individual level stress management interventions (SMI) at work were demonstrated, yet long-term effectiveness remains unexplored. We therefore aimed to address this research gap. Methods. 94 male middle managers participated in a randomized wait-list controlled trial between 2006 and 2008 and in a post-trial-follow-up survey in 2015. During the first two years, all received an 18-hour psychotherapeutic SMI intervention which was based on the Effort-Reward Imbalance (ERI) model: tackling stressor on mismatch between effort and reward and promoting recovery on overcommitment. Work stress (i.e., ERI indicators) was the primary outcome, and the secondary outcome was depressive symptoms. The long-term effectiveness of the SMI was examined by mixed modeling, using an external control group (n = 94 ). Results. Effort and reward were substantially improved with significant intervention ⁎ time interaction effects (p < 0.001 ) compared to the external control group; effects on overcommitment and depressive symptoms were also significant (p < 0.05 and p < 0.01, resp.), though their trajectories in the intervention group were less sustainable. Conclusions. The effectiveness of this psychotherapeutic SMI at work based on the ERI model was observed over a 9-year period, particularly on the effort-reward ratio.